Birth of Census Towns in India: An Economic Analysis. (December 2020) - Chakrabarti, Saumyabrata; Mukherjee, Vivekananda
In Indian census, the reclassification of villages as small towns (called census towns) has been startling during the decade 2001–2011 and accounted for almost 30 per cent of urbanization, which is significantly larger than their growth rate in previous decades. Though reclassified as towns, they are governed as rural settlements. This article applies urban economic theory along with rural–urban labour market dynamics to identify the factors behind the birth of census towns. It also attempts to empirically check the validity of some of the hypotheses of the theoretical model it develops by using data from the state of West Bengal during 2001–2011 where the growth rate of census towns had been one of the highest in India. It turns out that the higher formal sector income in the nearby urban centres with lower extent of urban sprawl is the major factor explaining the birth of census towns. JEL Classification: R11, R12, R23